Hubungan Faktor Budaya Dan Psikologi Terhadap Keputusan Pembelian Di Restoran-Restoran Kota Prabumulih - Amandin Amandin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
Along with the development of this modern era, for businesses the most in demand is the culinary business, marked by the number of businessmen who are involved in the culinary world. This study aims to determine the relationship between cultural and psychological factors on purchasing decisions in restaurants in Prabumulih. The method used in this research is a survey method. The data collected consists of primary data and secondary data. Primary data was obtained through the interview method which was equipped with prepared questionnaires. Secondary data were obtained from related restaurants, as well as several library sources in the form of journals and books related to this research. And the research design used is causal associative design. In this study, what will be analyzed is the relationship between cultural and psychological factors on customer loyalty in restaurants in the city of Prabumulih. The results show that the calculation of the coefficient of determination (R2) is used to find out how many percent of the variation in the dependent variable can be explained by variations in the independent variable, which is seen from the value of the dependent variable. Adjusted R square is 0.962, this means that 96.2% of the variation in the dependent variable of purchasing decisions at Prabumulih City Restaurants can be explained by the independent variables of cultural and psychological factors, while the remaining 0.38 or 3.8% is explained by other variables. outside variables other than cultural and psychological factors. Then the first hypothesis can be explained to have a significant and positive influence with the Adjusted R square value of 0.962 (96.2%) this shows that cultural and psychological factors are able to explain 96.2% of the variation of the purchasing decision variable. Keywords: Cultural Factors, Psychology and Purchasing Decisions